Differences in disease presentation between men and women with sarcoidosis: A cohort study. (January 2022) - Lundkvist, Amanda; Kullberg, Susanna; Arkema, Elizabeth V.; Cedelund, Kerstin; Eklund, Anders; Grunewald, Johan; Darlington, Pernilla
Abstract: Background: Sarcoidosis is an elusive disease due to its heterogeneity. It is well recognized that the clinical picture is dependent on ethnicity, organ involvement and age. However, data on the role of sex is inconsistent. We aimed to study the gender-related differences in disease presentation in Swedish patients with sarcoidosis. Subjects and methods: Clinical data was collected between 1996 and 2020, yielding a register with 1429 cases with sarcoidosis in a pulmonary clinic. The diagnosis was met according to WASOG criteria. Data on age, radiologic stage at the time of disease onset, and potential extra-pulmonary manifestations, was retrieved. Differences between men and women were analyzed with Fisher's Exact Test and t -test where appropriate. Results: In the register there were 61% men and they were approximately three years younger than the women at the time of diagnosis. Men presented with a more advanced radiographic stage on chest imaging compared to women, radiographic stage II (46% vs 36%, p < 0.001), while women compared to men more often had stage 0-I disease on pulmonary x-rays (6% vs 2%, p < 0.001 for stage 0 and 46% vs 38%, p < 0.01 for stage I). Women had more cutaneous involvement (13% vs 8%, p < 0.01) and more often involvement of salivary glands (3% vs 1%, p < 0.05). Conclusions: In this cohort with sarcoidosis patients, there was a predominance of men. They presented with more severe disease at a younger age, while women more often were found to have involvement of the skin and salivary glands. Highlights: Among sarcoidosis cases men were overrepresented and younger at disease onset. Men more often had radiographic stage II while stage 0-I were more common in women. Women more often had involvement of the skin and salivary glands. Abstract : Keypoints: We aimed to study differences between men and women with sarcoidosis. We found that men were overrepresented, in general younger at disease onset and had a more advanced radiographic stage on chest imaging compared to women.